The Stability of Temperament from Early Childhood to Early Adolescence:A Multi‐method, Multi‐informant Examination. Issue 2 (18th April 2018) - Kopala‐Sibley, Daniel C.; Olino, Thomas; Durbin, Emily; Dyson, Margaret W.; Klein, Daniel N.
Abstract: Temperament is a core aspect of children's psychological functioning and is assumed to be at least somewhat stable across childhood. However, little research has assessed the stability of temperament from early childhood to early adolescence. Moreover, few studies have examined the influence of measurement and analytic methods on the stability of early temperament over periods of more than a few years. We obtained laboratory observations and mother and father reports of temperamental negative and positive emotionality and effortful control from 559 three‐year‐olds. Approximately nine years later, children and both parents completed questionnaire measures of similar temperament constructs. Zero‐order correlations revealed greater within‐informant than cross‐informant stability. In addition, compared with parent reports, early childhood laboratory measures showed greater convergent and divergent validity with child, mother, and father reports at age 12. Finally, latent temperament variables at age 3 composed of laboratory and parent‐report measures and latent variables at age 12 composed of parent and child reports showed moderate stability. There was also a weak but significant association of early effortful control with later negative and positive emotionality. Results have implications for assessing temperament and knowledge of the stability of temperament across childhood. Copyright © 2018 European Association of Personality Psychology